Enhanced SWIR Light Detection in Organic Semiconductor Photodetectors through Up-Conversion of Mid-Gap Trap States - Zeiske, Stefan (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.